Subcarrier Multiple Access system using a single optical source to suppress Optical Beat Interference - Abdul-Rashid, H. A.; Al-Qdah, M. T.; Chuah, H. T.; Tayahi, M. B. (2007)
The authors propose, design and analyze a Subcarrier Multiple Access system using a single optical source to suppress Optical Beat Interference (OBI). A mathematical model is developed and an experiment is carried out to study the performance of the system. The experimental results are in agreement with the mathematical model, which show an OBI free transmission.